Dynamics of subpopulations of CD15+CD66b+ and CD62L+CD63+ circulating neutrophils in patients with benign neoplasms and progression of kidney cancer - I. R. Myagdieva; T. V. Abakumova; D. R. Dolgova; O. Yu. Gorshkov; T. P. Gening; R. Sh. Zaineeva; S. A. Timofeeva (Успехи молекулярной онкологии, 2025)
Introduction. Due to the ambiguous role of neutrophils in carcinogenesis, it is relevant to study their phenotypic transformation and subpopulation composition that determines protumor (CD15+CD66b+) or antitumor (CD62L+CD63+) potential.Aim. To assess the dynamics of CD15+CD66b+ and CD62L+CD6+ circulating neutrophil subpopulations in patients with benign neoplasms and during the progression of kidney cancer.Materials and methods. The study focused on circulating neutrophils from patients with benign neoplasms and kidney cancer. The phenotype of monopopulations (CD15+, CD66b+, CD62L+, CD63+, CD95+) and subpopulations (CD15+CD66b+, CD62L+CD63+) of neutrophils was assessed using flow cytometry (BioSino, China). Statistical analysis was performed using Statistica 13 and Jamovi 2.3.28.Results. A significant increase in the number of CD15+, CD62L+, and CD66b+ neutrophil monopopulations, as well as in the number of CD15+CD66b+ neutrophils, was observed in the groups of patients with benign kidney tumors and kidney cancer compared to the control group. In patients with benign renal tumors, the percentage of CD62L+CD63+  neutrophils was three times higher than in patients with stage I–II kidney cancer, and twice as high as in those with advanced kidney cancer. According to the Cox regression model, changes in the numbers of CD15+CD66b+ and CD62L+CD63+  neutrophils, alongside an increase in leukocyte count, serve as prognostic markers of kidney cancer in patients over 68 years of age.Conclusion. The number of circulating neutrophils with a protumor phenotype (CD15+CD66b+) increases even at the stage of benign kidney neoplasms compared to controls and remains elevated throughout all stages of carcinogenesis. Meanwhile, the number of circulating neutrophils with an antitumor phenotype (CD62L+CD63+) significantly increases in benign renal neoplasms but decreases during cancer progression. Assessment of the circulating neutrophil phenotype may help predict the risk of kidney neoplasms.